A Conceptual Design Optimization of Collimator With 181Ta as Neutron Source for Boron Neutron Capture Therapy Based Cyclotron Using Computer Simulation Program Monte Carlo N Particle Extended - Jans P B Siburian; Andang Widi Harto; Yohannes Sardjono (Indonesian Journal of Physics and Nuclear Applications, 2017)
The optimization of collimator with 30 MeV cyclotron as neutron source and 181Ta as its proton target. cyclotron assumed work at 30 MeV power with 1 mA and 30 kW operation condition. Criteria of design based on IAEA’s recommendation. Using MCNPX as simulator, the result indicated that with using 181Ta as target material with 0.55 cm thickness and 19 cm diameter, 25 cm and 45 cm PbF2 as reflector and back reflector, 30 cm 32S as a moderator, 20 cm 60Ni as fast neutron filter, 2 cm 209Bi as gamma filter, 1 cm 6Li2 CO3- polyethylenes as thermal neutron filter, and 23 cm diameter of aperture, an epithermal neutron beam with intensity 4.37 x 109 n.cm-2.s-1, fast neutron and gamma doses per epithermal neutron of 1.86 x 10-16 Gy.cm2.n-1 and 1.93 x 10-13Gy.cm2.n-1, minimum thermal neutron per epithermal neutron ratio of 0.003, and maximum directionality 0,728, respectively could be produced. The results have passed all the IAEA’s criteria.